Nucleic acid-based therapy for coronavirus disease 2019 (2020)
The coronavirus disease 2019 (COVID-19), the pandemic that originated in China has already spread into more than 190 countries, resulting in huge loss of human life and many more are at the stake of losing it; if not intervened with the best therapeutics to contain the disease. For that aspect, various scientific groups are continuously involved in the development of an effective line of treatment to control the novel coronavirus from spreading rapidly. Worldwide scientists are evaluating various biomolecules and synthetic inhibitors against COVID-19; where the nucleic acid-based molecules may be considered as potential drug candidates. These molecules have been proved potentially effective against SARS-CoV, which shares high sequence similarity with SARS-CoV-2. Recent advancements in nucleic acid-based therapeutics are helpful in targeted drug delivery, safely and effectively. The use of nucleic acid-based molecules also known to regulate the level of gene expression inside the target cells. This review mainly focuses on various nucleic acid-based biologically active molecules and their therapeutic potentials in developing vaccines for SARS-CoV-2.